Color Stability and Surface Roughness of a Laboratory‐Processed Composite Resin as a Function of Mouthrinse. Issue 5 (14th July 2015) - Cengiz, Seda; Yüzbaşioğlu, Emir; Cengiz, M. Inanç; Velioğlu, Neslin; Sevimli, Gaye; Paravina, Rade
Abstract Statement of the Problem Mouthrinses can cause discoloration on indirect resin composites. Purpose of the Study The purpose of the study was to investigate the effect of different mouthrinses on the color changes and surface roughness of a laboratory‐processed composite. Methods and Materials Fifty discs were made using GC Gradia/GC indirect composites and divided into five groups which immersed in artificial saliva and four different types of mouthrinses. The samples were immersed daily for 14 days in 20 mL of the solutions for 2 minutes twice a day (with a 12‐hour interval between exposures). Measurements were carried out at four different times: 1 hour after sample preparation (t0), 1 day (t1), 7 days (t2), and 14 days (t3) after the first immersion in the solutions. The color before and after immersion was measured according to Comission Internationale de L'Eclairage (CIE L*, a*, b*) System and ΔL*, Δa*, Δb*, and ΔE* values were calculated. The surface roughness Ra (μm) of the specimens was evaluated using a profilometer. Results There were significant differences between the groups at all time representing ΔE values (p < 0.001). At (t1) time representing ΔRa value, there were significant differences between the groups (p < 0.05). At (t2, t3) time representing ΔRa values, there were significant differences between the groups (p < 0.001). Pharmol Zn immersed specimens showed ΔE values between 1.04 and 3.67. Conclusions The result of this study indicated that the mouthrinses affected the color stability of indirect composites. Clinical Significance Based on the results of this study, patients with resin composite restorations should be warned by the dentists about the discoloration of the restorations and the time period of the mouthrinse that will be used.